Development of Brake System and Regenerative Braking Cooperative Control Algorithm for Automatic-Transmission-Based Hybrid Electric Vehicles - Ko, Jiweon; Ko, Sungyeon; Son, Hanho; Yoo, Byoungsoo; Cheon, Jaeseung; Kim, Hyunsoo (IEEE transactions on vehicular technology, 2015)
In this paper, a brake system for an automatic transmission(AT)-based hybrid electric vehicle (HEV) is developed, and a regenerative braking cooperative control algorithm is proposed, with consideration of the characteristics of the brake system. The brake system does not require a pedal simulator or a fail-safe device, because a hydraulic brake is equipped on the rear wheels, and an electronic wedge brake (EWB) is equipped on the front wheels of the vehicle. Dynamic models of the HEV equipped with the brake system developed in this study are obtained, and a performance simulator is developed. Furthermore, a regenerative braking cooperative control algorithm, which can increase the regenerative braking energy recovery, is suggested by considering the characteristics of the proposed hydraulic brake system. A simulation and a vehicle test show that the brake system and the regenerative braking cooperative control algorithm satisfy the demanded braking force by performing cooperative control between regenerative braking and friction braking. The regenerative braking cooperative control algorithm can increase energy recovery of the regenerative braking by increasing the gradient of the demanded braking force against the pedal stroke. The gradient of the demanded braking force needs to be determined with consideration of the driver's braking characteristics, regenerative braking energy, and the driving comfort.